ESTUDO COMPARATIVO DE PAINEIS DE VEDAÇÃO CONFECIONADOS COM CIMENTO PORTLAND E MATERIAIS ALCALI-ATIVADOS - Ramos, Lucas Thadeu da Silva; Santos, Jonatas Douglas Almeida; Baumbach, Miriam de Oliveira; Borges, Paulo Henrique Ribeiro; Oliveira, Raquel Diniz (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Alkali-activated materials (AAM) compared to Portland cement (PC) may significantly reduce the carbon dioxide emissions, as well as the consumption of non-renewable natural resources in civil engineering applications. This paper compares the performance of PC with AAM as binders in cementitious wall panels for cladding system in a hot and humid climate. In this case study natural aggregates used as mortars was replaced with tailing from iron-ore mining activities in the state of Minas Gerais, Brazil. The thermal property determined for the three mortars was Thermal Conductivity using a heat flow meter apparatus according to ISO 8301 (1999). After that, one-story house building simulation was carried out using the Energy Plus Software. The main room annual operative temperature provided by different wall panels was compared to the adaptive comfort range established on ASHRAE Standard 55/2013 for Belo Horizonte city, Brazil. Results show that building simulations can effectively contribute to validate a sustainable wall panels that provide suitable human thermal conditions in hot and humid climate.